Preparation method for additive manufacturing of ODS-TA15 titanium alloy
By adding nano Y2O3 particles to TA15 titanium alloy and using selective laser melting technology to prepare ODS-TA15 titanium alloy, the problem of insufficient mechanical performance under high-temperature service conditions was solved, and the high-temperature mechanical performance of titanium alloy was improved and the controllability and cost reduction of manufacturing processes.
Patent Information
- Application Number
- CN202411319088.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2024-12-13
AI Technical Summary
The existing TA15 titanium alloy cannot meet the high-temperature mechanical performance requirements of aerospace vehicles under high-temperature service conditions, and traditional manufacturing processes have problems such as many processes, long cycles and high costs.
Using the additive manufacturing method, TA15 alloy powder was prepared by electrode induction aerosolization method and nano Y2O3 particles were added. ODS-TA15 titanium alloy was prepared by selective laser melting technology, and annealing was performed to optimize the microstructure of the alloy to improve mechanical properties.
It has achieved the improvement of the high-temperature mechanical properties of titanium alloy, refinement of microstructure, increased the ɑ/β phase interface, hindered dislocation movement, significantly improved the high-temperature deformation ability and mechanical properties of titanium alloy, and the preparation process is controllable and the cost is relatively Lower.
Smart Images

Figure CN119114972A_ABST
Abstract
Description
Technical Field
[0002] The present invention relates to the technical field of high-performance metal material preparation, and in particular to a method for preparing an ODS-TA15 titanium alloy by additive manufacturing. Background Art
[0003] As aerospace vehicles are developing rapidly towards high speed, large size, complex structure and functional integration, important aircraft structural parts have put forward higher requirements on the mechanical properties of materials. Titanium alloys are widely used in aerospace vehicles due to their advantages such as high specific strength, corrosion resistance and high temperature resistance. However, titanium alloys have high deformation resistance and are difficult to deform during the forming process. In addition, there are many processes, long cycles and high costs in the traditional manufacturing process, which makes it difficult to meet current manufacturing needs. Selective laser melting (SLM) technology is an emerging manufacturing technology that melts metal powder layer by layer to produce solid parts. It has strong forming ability and high forming accuracy for complex structures. It can effectively solve the problem of difficult forming of complex parts of titanium alloy as a whole, and has become one of the most important ways to manufacture complex aerospace structures. In recent years, selective laser melting (SLM) technology has attracted attention and application in the industry in the preparation of titanium alloy components.
[0004] As a widely used near-α-type titanium alloy, TA15 alloy has good room temperature strength and high temperature strength, high temperature resistance and welding performance. Because two β-stabilizing elements Mo and V are added to the alloy, TA15 alloy has the common characteristics of α-type titanium alloy and α+β titanium alloy. It can work for a long time (more than 3000h) at 500℃ and can be used to manufacture complex structure aircraft parts in the aerospace field, which can improve the structural reliability of aircraft to a certain extent. However, for higher service temperatures, the existing TA15 alloy can no longer meet the requirements, and only other titanium alloys with better high temperature mechanical properties can be developed or selected. Summary of the invention
[0005] In view of the above problems in the prior art, the present invention aims to provide a method for preparing an ODS-TA15 titanium alloy material suitable for high temperature service conditions.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing an additively manufactured ODS-TA15 titanium alloy comprises the following steps: S1: Raw material preparation TA15 alloy powder and nano Y2O3 particles prepared by electrode induction atomization method; wherein: the mass percentage of TA15 alloy powder is: Al: 5.5-7.0%, Zr: 1.5-2.5%, Mo: 0.5-2.0%, V: 0.8-2.5%, and the rest is Ti; Equipment and tooling preparation: mechanical ball mill testing machine, selective laser melting equipment, tubular heat treatment furnace, vacuum drying oven; S2: Pre-preparation The nano Y2O3 particles prepared in step S1 are mixed with TA15 alloy powder, wherein the mass percentage of the nano Y2O3 particles is 0.1-1%; after mixing, they are added into a mechanical ball mill tester and mixed into a uniform composite powder by a mechanical ball milling method; the mixing ball-to-material ratio is 1-4:1, the ball milling speed is 80-120 rpm, the ball tank is rotated upside down 360° during the ball milling mixing process, and the mixing time is 4-8 h; The composite powder mixed evenly in step ① is placed in a vacuum drying oven for drying; S3: Selected area laser printing The composite powder after drying in step ② of stage S2 is placed in the powder pool of the selective laser melting equipment prepared in step ② of stage S1, and the printing parameters are set to prepare the alloy. After the alloy printing is completed, air cooling is performed to obtain the TA15+Y2O3 alloy; S4: Annealing The TA15+Y2O3 alloy prepared in stage S3 is placed in a tubular heat treatment furnace for annealing to obtain the desired titanium alloy.
[0007] Preferably, the size of the nano Y2O3 particles in step S1 is 30 nm.
[0008] Preferably, in stage S3, the printing parameters of the selective laser melting equipment are: laser power 220-240 W, laser scanning speed 850-1250 mm / s, laser scanning spacing 0.10-0.14 mm, layer thickness 30 μm, scanning strategy is checkerboard mode, the length and width of the checkerboard are both 5 mm, and argon protection.
[0009] Preferably, in stage S4, the annealing heating rate is 10°C / min, the holding temperature is 500-900°C, argon gas is introduced during the holding process for protection, the holding time is 2-4 h, and the cooling medium is air.
[0010] Preferably, in step ① of stage S2, when the nano Y2O3 particles are mixed with the TA15 alloy powder, the mass percentage of the nano Y2O3 particles is 0.1±0.05%.
[0011] Preferably, in stage S4, the holding temperature is 900° C. and the holding time is 4 h.
[0012] The idea of the present invention is that, as far as titanium alloys are concerned, excellent mechanical properties can be obtained by optimizing the chemical composition of the alloy and regulating the microstructure. Oxide dispersion strengthened (ODS) metal materials have attracted the attention of material researchers because of their better high-temperature mechanical properties. By adding nano Y2O3 particles to the metal matrix, the Y2O3 particles with a higher melting point can play a role in refining grains and hindering dislocation operation, optimizing the microstructure of the metal and obtaining ideal mechanical properties. For example, when Y2O3 particles are added to the Ti6Al4V alloy, Y2O3 can be activated as a nucleation point and promote the equiaxed transformation of the α phase, the size of the α phase is significantly reduced, excellent plasticity is provided, and the yield strength and tensile strength are further improved. Therefore, in order to further improve the high-temperature mechanical properties of the TA15 alloy, the strengthening effect of Y2O3 nanoparticles can be used to prepare a TA15 alloy with good high-temperature mechanical properties.
[0013] Compared with the prior art, the present invention has the following advantages: (1) The additive manufacturing method of the ODS-TA15 titanium alloy of the present invention is convenient and controllable. By adding nano Y2O3 particles, due to the high melting point, the nano Y2O3 particles will not melt during the SLM forming process of the TA15 alloy and can act as nucleation particles to promote nucleation, so that the TA15 alloy forming grains are equiaxed and refined, and finally a fine and uniform microstructure is obtained. In addition, the addition of nano Y2O3 particles is also beneficial to SLM forming.
[0014] (2) The TA15 alloy prepared by selective laser obtains α′ phase during air cooling due to the fast cooling rate. In the subsequent annealing process, a lamellar ɑ+β phase structure will be obtained. Y2O3, as nanoparticles, is pinned on the ɑ / β phase interface, hindering the migration of the phase interface, thereby reducing the growth tendency of the ɑ flakes. As a result, the alloy obtains a fine lamellar ɑ+β phase structure during annealing, increasing the number of ɑ / β phase interfaces and the proportion of them in the microstructure. It can significantly hinder dislocation movement during high temperature deformation and play a good strengthening role.
[0015] (3) Nano Y2O3 particles with a size of about 20-30 nm are distributed in the TA15 alloy matrix prepared by the method of the present invention. During the deformation of the alloy at high temperature, a large number of dislocations can be found around the nano Y2O3 particles, which play an obvious role in pinning dislocations. Therefore, there is an interaction between the nano Y2O3 particles and the dislocations in the TA15 alloy, which plays a role in dispersion strengthening, so that the TA15 alloy has good high-temperature mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a flow chart of Example 1 of the present invention; Figure 2 The microstructure of Example 1 of the present invention; Figure 3The microstructure of Example 2 of the present invention; Figure 4 The microstructure of Example 3 of the present invention; Figure 5 The microstructure of Example 4 of the present invention; Figure 6 This is the microstructure of Example 5 of the present invention. DETAILED DESCRIPTION
[0017] The preparation method of the present invention is now described in detail in conjunction with specific embodiments so that those skilled in the art can fully understand and implement it. Example 1
[0018] S1: Raw material preparation TA15 alloy powder (the mass percentage of TA15 alloy powder components is: Al: 6.7%, Zr: 1.8%, Mo: 1.0%, V: 1.5%, and the rest is Ti) and nano Y2O3 powder particles (specification is 30 nm) prepared by electrode induction atomization method.
[0019] Equipment and tooling preparation: mechanical ball mill testing machine (including matching stainless steel ball mill jars and ball mill beads), selective laser melting equipment (laser power 220~240W, laser scanning speed 850~1250 mm / s, laser scanning spacing 0.10~0.14mm, layer thickness 30μm, scanning strategy is checkerboard mode, checkerboard length and width are both 5mm, argon protection), tubular heat treatment furnace, vacuum drying oven.
[0020] S2: Pre-preparation The nano Y2O3 powder prepared in step ① of stage S1 was added into a mechanical ball mill at a mass percentage of 0.1% and TA15 alloy powder, and mixed into a uniform composite powder by mechanical ball milling; the ball-to-material ratio was 1:1, the rotation speed was 80 rpm, the ball tank was rotated 360° upside down during the ball milling mixing process, and the mixing time was 4 h.
[0021] The composite powder mixed and stirred evenly in step ① is placed in a vacuum drying oven for drying.
[0022] S3: Selected area laser printing The mixed alloy powder after drying treatment in step ② of stage S2 was placed in the powder pool of the selective laser melting equipment prepared in step ② of stage S1, and the printing parameters were set (laser power of 220 W, scanning speed of 1050 mm / s, scanning spacing of 0.12 mm, layer thickness of 30 μm, scanning strategy of checkerboard mode, checkerboard length and width of 5 mm, argon protection), and the alloy was prepared. After the alloy printing was completed, it was air-cooled to obtain an alloy with a composition of 99.9wt.% TA15-0.1wt.% Y2O3.
[0023] S4: Annealing The 99.9wt.%TA15-0.1wt.%Y2O3 alloy prepared by selective laser printing in stage S3 was placed in a heat treatment furnace for annealing. The annealing heating rate was 10℃ / min, the holding temperature was 900±10℃, argon gas was introduced during the holding process, the holding time was 4h, and the cooling medium was air.
[0024] like Figure 1 This is a flow chart of this embodiment; Figure 2 The metallographic microstructure diagram of this embodiment is shown. The 99.9wt.%TA15-0.1wt.%Y2O3 alloy steel prepared according to the method of this embodiment has a fine needle-like α′ phase structure due to the fast air cooling speed; after annealing at 900±10℃ for 4 hours, the microstructure is composed of coarse flake α phase and β phase, and a small amount of Y2O3 nanoparticles with a size of 20-30nm are distributed on the α phase matrix; so that the tensile strength of the titanium alloy at room temperature is 1097MPa, the yield strength is 985MPa, and the elongation after fracture is 15.57%. The tensile strength at 500℃ is 696MPa, the yield strength is 568MPa, and the elongation after fracture is 17.04%. Example 2
[0025] The three stages of S1 raw material preparation, S3 selected area laser printing and S4 annealing treatment are the same as those in Example 1, except that: S2: Pre-preparation ① Add 0.4% by mass of the nano Y2O3 powder prepared in step ① of stage S1 and TA15 alloy powder into the mechanical ball mill prepared in step ② of S1; like Figure 3 The metallographic microstructure of this embodiment is shown. The 99.9wt.%TA15-0.4wt.%Y2O3 alloy steel prepared according to the method of this embodiment has a fine needle-like α′ phase structure due to the fast air cooling speed. After annealing at 900±10℃ for 4 hours, the microstructure is composed of lamellar α phase and β phase, but the thickness of the α phase is smaller than that of Example 1, and Y2O3 nanoparticles with a certain size of 20~30 nm are distributed on the α phase matrix; so that the tensile strength of the titanium alloy at room temperature is 1049 MPa, the yield strength is 953 MPa, and the elongation after fracture is 13.18%. The tensile strength at 500℃ is 715 MPa, the yield strength is 597 MPa, and the elongation after fracture is 17.42%. Example 3
[0026] The three stages of S1 raw material preparation, S3 selected area laser printing and S4 annealing treatment are the same as those in Example 1, except that: S2: Pre-preparation ① Add 1.0% by mass of the nano Y2O3 powder prepared in step ① of stage S1 and TA15 alloy powder into the mechanical ball mill prepared in step ② of S1; like Figure 4 The metallographic microstructure of this embodiment is shown. The 99.9wt.%TA15-1.0wt.%Y2O3 alloy steel prepared according to the method of this embodiment has a fine needle-like α′ phase structure due to the fast air cooling speed. After annealing at 900±10℃ for 4 hours, the microstructure is composed of fragmented ɑ phase and β phase, and a large number of Y2O3 nanoparticles with a size of 20~30 nm are distributed on the ɑ phase matrix; so that the tensile strength of the titanium alloy at room temperature is 1067MPa, the yield strength is 982MPa, and the elongation after fracture is 12%. The tensile strength at 500℃ is 749MPa, the yield strength is 644MPa, and the elongation after fracture is 10.59%. Example 4
[0027] The three stages of S1: raw material preparation, S2: pre-preparation and S3: selected area laser printing are the same as those in Example 2, except that: In stage S4: the temperature is raised to 500 °C and the holding time is 4 ± 0.5 h; like Figure 5 The metallographic microstructure of this embodiment is shown. The 99.9wt.%TA15-0.1wt.%Y2O3 alloy steel prepared according to the method of this embodiment has a fine needle-shaped α′ phase structure due to the fast air cooling speed. After annealing at 500±10℃ for 4 hours, the microstructure is composed of fine needle-shaped ɑ phase and β phase, and a small amount of Y2O3 nanoparticles with a size of 20~30nm are distributed on the ɑ phase matrix; so that the tensile strength of the titanium alloy at room temperature is 1339 MPa, the yield strength is 1249 MPa, and the elongation after fracture is 5.84%. The tensile strength at 500℃ is 910 MPa, the yield strength is 784 MPa, and the elongation after fracture is 9.74%. Example 5
[0028] The three stages of S1 raw material preparation, S3 selected area laser printing and S4 annealing treatment are the same as those in Example 1, except that: S2: Pre-preparation ① Take an appropriate amount of the TA15 alloy powder prepared in step ① of stage S1 (without adding the nano-Y2O3 powder) and put it into the drying oven prepared in step ① for drying; like Figure 6The metallographic microstructure of this embodiment is shown. The 100wt.%TA15 alloy steel prepared according to the method of this embodiment has a fine needle-like α′ phase structure due to the fast air cooling speed. After annealing at 900±10℃ for 4 hours, the microstructure is composed of lamellar α phase and β phase. There are no nanoparticles on the matrix. As a result, the tensile strength of the titanium alloy at room temperature is 956 MPa, the yield strength is 851 MPa, and the elongation after fracture is 14.05%. The tensile strength at 500℃ is 632 MPa, the yield strength is 567 MPa, and the elongation after fracture is 17.16%.
[0029] The above embodiments are only preferred embodiments of the present invention and are not any formal limitations on the present invention. Any technician familiar with the art can use the above disclosed methods to make many possible changes and modifications to the technical solution of the present invention without departing from the technical principle and solution scope of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any combination, modification or replacement of the technical features disclosed in the present invention based on the technical essence of the present invention without departing from the principle or solution of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing ODS-TA15 titanium alloy by additive manufacturing, characterized in that: The steps include: S1: Raw material preparation TA15 alloy powder and nano Y2O3 particles prepared by electrode induction atomization method; wherein: the mass percentage of TA15 alloy powder is: Al: 5.5-7.0%, Zr: 1.5-2.5%, Mo: 0.5-2.0%, V: 0.8-2.5%, and the rest is Ti; Equipment and tooling preparation: mechanical ball mill testing machine, selective laser melting equipment, tubular heat treatment furnace, vacuum drying oven; S2: Pre-preparation The nano Y2O3 particles prepared in step S1 are mixed with TA15 alloy powder, wherein the mass percentage of the nano Y2O3 particles is 0.1-1%; after mixing, they are added into a mechanical ball mill tester and mixed into a uniform composite powder by a mechanical ball milling method; the mixing ball-to-material ratio is 1-4:1, the ball milling speed is 80-120 rpm, the ball tank is rotated upside down 360° during the ball milling mixing process, and the mixing time is 4-8 h; The composite powder mixed evenly in step ① is placed in a vacuum drying oven for drying; S3: Selected area laser printing The composite powder after drying in step ② of stage S2 is placed in the powder pool of the selective laser melting equipment prepared in step ② of stage S1, and the printing parameters are set to prepare the alloy. After the alloy printing is completed, air cooling is performed to obtain the TA15+Y2O3 alloy; S4: Annealing The TA15+Y2O3 alloy prepared in stage S3 is placed in a tubular heat treatment furnace for annealing to obtain the desired titanium alloy.
2. The method for preparing an additively manufactured ODS-TA15 titanium alloy according to claim 1, characterized in that: The specification of the nano Y2O3 particles in step S1 is 30 nm.
3. The method for preparing ODS-TA15 titanium alloy by additive manufacturing according to claim 2, characterized in that: In stage S3, the printing parameters of the selective laser melting equipment are: laser power 220~240W, laser scanning speed 850~1250 mm / s, laser scanning spacing 0.10~0.14 mm, layer thickness 30μm, scanning strategy is checkerboard mode, the length and width of the checkerboard are both 5mm, and argon protection.
4. The method for preparing ODS-TA15 titanium alloy by additive manufacturing according to claim 3, characterized in that: In stage S4, the annealing heating rate is 10°C / min, the holding temperature is 500-900°C, argon gas protection is introduced during the holding process, the holding time is 2-4 h, and the cooling medium is air.
5. The method for preparing ODS-TA15 titanium alloy by additive manufacturing according to claim 1, characterized in that: In step ① of stage S2, when the nano Y2O3 particles are mixed with the TA15 alloy powder, the mass percentage of the nano Y2O3 particles is 0.1±0.05%.
6. The method for preparing ODS-TA15 titanium alloy by additive manufacturing according to claim 4, characterized in that: In stage S4, the holding temperature is 900° C. and the holding time is 4 h.
